Electrochemical Determination of B-Type Natriuretic Peptide with an Epitope-Imprinted Polymer-Based Sensor - Liu, Kai-Hsi; Thomas, James L.; Chu, Pei-Chia; Ciou, Jing-Chen; Chen, Chuen-Yau; Lin, Hung-Yin; Lee, Mei-Hwa (Biosensors (Basel), 2024)
B-type natriuretic peptides (BNP) are produced and secreted by the myocardium to reduce blood pressure and cardiac load. They cause vasodilation, natriuresis, growth suppression, and inhibition of the sympathetic nervous system and the renin–angiotensin–aldosterone system. The measurement of plasma BNP levels provides clinically useful information concerning the diagnosis and management of left ventricular dysfunction and heart failure, complementing other diagnostic testing procedures. In this work, three epitopes from the N-terminal (BNPnt), C-terminal (BNPct), and the cystine-bridged cyclic peptides (BNPr) of B-type natriuretic peptides were synthesized as templates for molecular imprinting. These peptides were doped into aniline (AN) and m-aminobenzenesulfonic acid (MSAN) for electropolymerization, thus forming epitope-imprinted poly(AN-co-MSAN) conductive films (EIPs). The monomer ratio was optimized using the electrochemical signals during polymerization. The optimized films were then characterized using a scanning electron microscope (SEM), atomic force microscope (AFM), and AC impedance. The electrochemical response of the films to the target peptides and to BNP was then measured. The sensing range of the EIPs-coated electrodes was from 0.001 to 1000 pg/mL for BNP. Finally, the BNP concentration in diluted serum samples was measured with the BNPrIP-coated electrode, giving 3.15 ± 0.07 pg/mL. By spiking the sample with known BNP concentrations, the accuracy was determined to be better than ±5%.